2014
DOI: 10.1371/journal.pone.0111548
|View full text |Cite|
|
Sign up to set email alerts
|

Antiapoptotic Factor Humanin Is Expressed in Normal and Tumoral Pituitary Cells and Protects Them from TNF-α-Induced Apoptosis

Abstract: Humanin (HN) is a 24-amino acid peptide with cytoprotective action in several cell types such as neurons and testicular germ cells. Rattin (HNr), a homologous peptide of HN expressed in several adult rat tissues, also has antiapoptotic action. In the present work, we demonstrated by immunocytochemical analysis and flow cytometry the expression of HNr in the anterior pituitary of female and male adult rats as well as in pituitary tumor GH3 cells. HNr was localized in lactotropes and somatotropes. The expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 49 publications
2
32
0
Order By: Relevance
“…We speculated that embryonic brain outcomes mirror others' findings in adult brain of mHN upregulation after neurologic injury (Chin et al, 2013;Gottardo et al, 2014;Hashimoto et al, 2001). A limitation of having a restricted sample size for sex-specific determinations exists, yet sex-specific differences emerged.…”
Section: Discussionmentioning
confidence: 89%
“…We speculated that embryonic brain outcomes mirror others' findings in adult brain of mHN upregulation after neurologic injury (Chin et al, 2013;Gottardo et al, 2014;Hashimoto et al, 2001). A limitation of having a restricted sample size for sex-specific determinations exists, yet sex-specific differences emerged.…”
Section: Discussionmentioning
confidence: 89%
“…showing inhibition of TNF-α induced apoptosis by HN in anterior pituitary cells gonadectomized female and male rats. [40]…”
Section: Discussionmentioning
confidence: 99%
“…The cytoprotective effects of HN and HNr have been described in different cell types including neurons (Zapala et al 2010;Sponne et al 2004), pancreatic β cells (Hoang et al 2010), testicular germ cells, and Leydig cells (Lue et al 2010). We have previously shown that HN exerts an antiapoptotic effect in anterior pituitary cells from both female and male rats as well as in GH3 cells (Gottardo et al 2014).…”
Section: Introductionmentioning
confidence: 98%